Pelatihan TOEFL Dengan Pendekatan Circ Untuk Mencapai Nilai Ideal Di Masa Pandemi - Syamsurrijal, Syamsurrijal; Ceriyani Miswaty, Titik; Zaki Pahrul Hadi, Muhammad (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
This community service aims to provide not only knowledge but also readiness to face the TOEFL (Test of English as Foreign Language) exam for students and lecturers in West Nusa Tenggara. This community service is carried out online using zoom technology as a learning medium for one month. The target community is the campus community, namely students and lecturers from various universities in West Nusa Tenggara. The method used in this community service is the Cooperative Integrated Reading and Composition (CIRC) method, where participants are divided into several groups, then given tips and strategies in answering the TOEFL test. Each group discussed and exchanged ideas in answering all the questions in the TOEFL. The cost of this community service activity is fully sourced from the service implementation team. After the implementation of this community service activity, participants have the ability and readiness as well as a quite significant score than before.